Mental Health in Islamic Education Curriculum: Challenges and Future Prospects - Yudelnilastia, Yudelnilastia; Rahmanita, Rahmanita; Susanti, Weti; Wardiantoni, Wardiantoni (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
Mental health is a crucial aspect in individual development, especially in Islamic education that emphasizes the balance between spiritual and psychological aspects. This article aims to analyze the integration of mental health in the Islamic education curriculum as well as the challenges and prospects in its implementation. This study uses a qualitative descriptive approach with content analysis. Data were collected through articles with Sinta-accredited journals, books, and relevant research data from Google Scholar, DOAJ, Moraref, and Google Books with a publication period of 2015-2025. The results of the study indicate that although there is awareness of the importance of mental health in Islamic education, implementation in the curriculum still faces various challenges, such as a lack of resources, limited understanding, and resistance from some parties. However, there are positive prospects with the emergence of an Islamic psychology-based approach that can be applied in education. This article recommends the need for collaboration between academics and education practitioners to design a curriculum that is more responsive to mental health issues.